Accelerated testing and validation : testing, engineering, and management tools for lean development - Porter, Alex (Newnes, 2004)
Accelerated Testing and Validation Methods is a cross-disciplinary guide that describes testing and validation tools and techniques throughout the product development process. Alex Porter not only focuses on what information is needed but also on what tools can produce the information in a timely manner. From the information provided, engineers and managers can determine what data is needed from a test and validation program and then how to select the best, most effective methods for obtaining the data. This book integrates testing and validation methods with a business perspective so readers can understand when, where, and how such methods can be economically justified. Testing and validation is about generating key information at the correct time so that sound business and engineering decisions can be made. Rather than simply describing various testing and validation techniques, the author offers readers guidance on how to select the best tools for a particular need, explains the appropriateness of different techniques to various situations and shows how to deploy them to ensure the desired information is accurately gathered. * Emphasizes developing a strategy for testing and validation * Companion CD includes example spreadsheets, program source code, case studies, video clips and much more * Teaches how to design a testing and validation program that deliver information in a timely and cost-effective manner.